2018
DOI: 10.1016/j.berh.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding the pathophysiology of spondyloarthritis

Abstract: Progressive understanding of the underlying pathophysiology of axial spondyloarthritis has successfully translated into innovative therapeutic strategies and successful management of patients in the clinic. This review summarizes the key roles of pro-inflammatory cytokines tumor necrosis factor and interleukin-17 in the onset and progression of disease and how these cytokines are instrumental in shaping the concept that enthesitis is a key feature of axial spondyloarthritis. Advances in immunological technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…Therefore, the effect of the IL-17A blocking agent on the bone would be more relevant to study in patients with postmenopausal osteoporosis or in a subgroup of patients with significant bone loss. Second, new advances in the understanding of bone remodeling in spondyloarthropathies has shown that other factors other than inflammation (mechanical stress, microbiota) can play a major role in the development of the bone loss phenotype observed in patients [63]. Finally, translating data from mice to human is always challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the effect of the IL-17A blocking agent on the bone would be more relevant to study in patients with postmenopausal osteoporosis or in a subgroup of patients with significant bone loss. Second, new advances in the understanding of bone remodeling in spondyloarthropathies has shown that other factors other than inflammation (mechanical stress, microbiota) can play a major role in the development of the bone loss phenotype observed in patients [63]. Finally, translating data from mice to human is always challenging.…”
Section: Resultsmentioning
confidence: 99%
“…The structural destruction and replacement of cartilage by granulation tissue is an important pathological change observed in AS patients. 11 Actually, an abnormal cartilage structure might be a common change before osteophyte formation. In 2009, Benjamin et al 34 applied IHC assay to spine osteophytes from the elderly and found a mixture of bone, cartilage, blood vessels and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Taken together, these results suggest that blood vessel invasion is closed related to cartilage destruction and calcification. 11 However, the mechanism of blood vessel invasion remains unknown. As we showed above, Currently, whether ERS plays a role in AS development remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Over the last 20 years, the greatly improved knowledges of underlying pathogenic mechanisms of AS, including the role of tumor necrosis factor (TNF), the interleukin 23/Th17 axis, and interleukin-17 , constituted the rationale to develop biologics selectively inhibiting these pathways. 9 For more than 10 years, anti-TNF biologics were successfully employed to treat AS, with marked improvement of signs and symptoms in around 60% of the patients. 10 Moreover, these biologics were demonstrated to inhibit the radiographic progression of AS when employed in early phase of the disease.…”
Section: Introductionmentioning
confidence: 99%